(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
This article examines the fundamental methodologies for the financial and economic assessment of investment projects. It explores a range of evaluation techniques, including discounting approaches, profitability metrics, and risk analysis, supplemented with personal insights and recommendations.